An IoT Architecture as a means of Optimizing Downy and Powdery Mildew Diseases Recognition in Portuguese Vineyards - Gomes, Bruno Pedrosa (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management